Effects of Verbena and Polygonum cuspidatum on growth performance, immune functions, cecal microbiota, and brain metabolites in Sansui ducks - Zhu, Yongcai; Wu, Qiaoqun; Luo, Linli; Yang, Shenglin (Frontiers in Veterinary Science, 2025)
Verbena and Polygonum cuspidatum, recognized for their antioxidant and immunomodulatory properties, have demonstrated potential benefits. However, the specific mechanisms by which these herbs impact poultry health, particularly regarding alterations in gut microbiota and brain metabolite profiles, remain insufficiently investigated. This study aimed to investigate the effects of Verbena and Polygonum cuspidatum supplementation on the growth performance, immunity, cecal microbiota, and brain metabolites in Sansui ducks. A total of 216 one-day-old ducks were randomly assigned to three treatments for a 35-day trial, each with 6 replicates of 12 ducks. The dietary treatments included a basal diet (T3), a basal diet supplemented with 40 mg/kg Verbena (T1), and a basal diet supplemented with 40 mg/kg Polygonum cuspidatum (T2). The results showed that both Verbena and Polygonum treatments significantly improved final body weight (by 3.0 and 4.1%, respectively) and increased serum IgG and IgM levels by 7.4 and 9.0%, and decreased feed conversion rates by 5.4 and 5.0%, respectively, compared to the control (p < 0.05). Notably, Verbena supplementation significantly increased the relative abundance of Bacteroidetes and Saccharibacteria, and significantly decreased the relative abundance of Actinobacteria compared to the control group (p < 0.05). Polygonum cuspidatum treatment increased the relative abundance of Megamonas compared to the control group (p < 0.05). Brain metabolite analysis showed that Verbena increased glutamine (Gln) levels by 18.4% and decreased γ-aminobutyric acid (GABA), tyrosine (Tyr), and acetylcholine (Ach) by 19.7, 14.6, and 22.5%, respectively (p < 0.05). Polygonum cuspidatum increased 5-Hydroxyindoleacetic acid (5-HIAA) concentration by 31.2% (p < 0.05). Correlation analysis indicated associations between gut microbiota (Villanella, Anaerosporobacter, Anaerofustis, and Flavonifractor) changes and brain metabolites (GABA, Ach, and Glutamic [Glu]), suggesting the potential influence of these herbs through the microbiota-gut-brain axis. Supplementation with Verbena officinalis and Polygonum cuspidatum enhanced growth performance, immunity, and brain neurochemical profiles, potentially through gut microbiota modulation. These herbs show promise as functional feed additives in duck production.